Peningkatan pelayanan publik pemerintah desa melalui sistem informasi kependudukan berbasis web - Riko, Dandi; Marcus, Ronald David (Journal of Information System and Application Development, 2023)
The rapid development of technology encourages faster and easier digitization of government administration services. The application of technology can be used to improve public services, especially at the village level. The purpose of this research is to develop a web-based population information system for village governments. The research was conducted through a Research and Development approach. The system is designed by involving four actors, namely admin, officers, residents, and the village head. Implementation is carried out by providing features on the website, from letter requests to complaint services. Then, the results of system development were tested using the Blackbox Testing and User Acceptance Test methods. The results show that the population information system developed is considered good enough to be used. Through this research, the performance of village officials in terms of service and management of population data can be optimized effectively and efficiently. In addition, the system built can also provide easier access to information for the community.